(untitled) (African Journal of Biomedical Research, 2023)
Presently artemisinin-based combination therapies (ACT) are now widely recommended as first-line treatment of uncomplicated malaria, however there are some reports and evidence of treatment failure despite adequate drug concentrations. Addition of a second long-acting partner drug to the existing single partner artemisinin-based combination therapy may delay the development of resistance. The objective of the present study is to determine the efficacy, of a triple combination of artemether-lumefantrine and amodiaquine in laboratory rodents. The blood schizonticidal activity of the proposed triple combination of artemether-lumefantrine (AL) and amodiaquine (AQ) was evaluated in a rodent model of Plasmodium berghei. Animals were treated orally with standard doses of artemether-lumefantrine (AL), amodiaquine (AQ) or the triple combination (ALAQ). Parasitological activity and survival of the animals were assessed over 24 days. Safety and plasma concentrations of artemether, amodiaquine and lumefantrine were determined both in the standalone and in the triple combination treatment groups using uninfected but treated albino rats There was a progressive significant decline in parasitemia in all therapeutic groups with the triple combination (ALAQ) achieving a 100% suppression of parasites by day 16. ALAQ resulted in significant elevations in total white blood cell counts, platelet counts, alanine transaminase and urea levels. There were significant reductions in blood pressure and heart rate. Compared to artemether-lumefantrine administered alone the triple combination (ALAQ) showed lower plasma artemether levels and area under the curve (AUC) values at 72hours with low day 7 lumefantrine plasma levels in the triple combination (ALAQ). These preliminary results showed that the triple therapy‘s efficacy, safety and pharmacokinetics are quite encouraging. Human studies are required to confirm the efficacy, safety and pharmacokinetic findings in this study.